Experimental study on shear wave velocity of sand-gravel mixtures considering the effect of gravel content - Cheng, Ke; Wu, Hao; Fang, Yi; Wu, Qi (Frontiers in Earth Science, 2023)
Sand-gravel mixtures are special engineering geological materials between soils and fractured rocks. This study performs a series of bending element tests to systematically investigate the shear wave velocity (Vs) of the sand-gravel mixtures, establish an effective evaluation method, and assess the influence of relative density and effective confining pressure on mixtures with a wide range of gravel contents. The results showed that the shear wave velocity increases and then decreases with the increase in gravel content and increases with the rise in relative density and effective confining pressure. Furthermore, a shear wave velocity prediction model is proposed in this study based on the intergranular contact state theory, including the stress parameter (n) and skeleton void ratio. The stress parameter can be described by a power function considering the uniformity coefficient. The model serves as a reference guide for estimating the shear wave velocity of sand-gravel mixtures with a wide range of gravel contents.